Live-in Tajuk: Role-Play Model in the Co-Creation of Community-Based Design Practices - Riskiyanto, Resza; Abdul Latip, Nurul Syala; Pasopati, Maheswara Rizky; Putri Agung, Brandi Orbita Imagi (ASEAN Journal of Community Engagement, 2025)
This article examines a collaborative project that involves diverse actors in the co-creation of community-based design within an agricultural context. This study focuses on the implementation of the role-playing model as a practice that cultivates empathy, reflexivity, and collective agency among actors. The model is implemented through several methods, including collective reading of the context, dynamic role shifting, and the negotiation of architectural program. As part of community service, this seven-day program involved four groups, each consisting of four local students and two international students, four lecturers and design practitioners, and four household units, to participate in the role-playing and co-creation in designing for the community in Tajuk Village, Central Java, Indonesia. The exploration revealed that the co-creation process emphasizes the fluidity of roles, highlighting a dynamic decision-making process in which authority is distributed and continually reconfigured. Knowledge is co-produced through reciprocal engagement, enabling the integration of multiple perspectives into the design process. Furthermore, the role-playing model contributes to the broader discourse of participatory design study, offering a flexible and integrative framework that supports inclusive and sustainable community development by merging description, interpretation, and critical analysis by and for the community.